DEVELOPMENT OF MULTIFUNCTIONAL CUBOID APE TO STIMULATE MOTOR ACTIVITIES IN CHILDREN AGED 4-5 YEARS IN PAUD ISTIQOMATUDDIN NURUL MU'ARIF PIDIE - Putri Rahmi; zikra hayati (JURNAL ILMIAH DIDAKTIKA: Media Ilmiah Pendidikan dan Pengajaran, 2023)
Based on the author's initial observations at PAUD Istiqamatuddin Nurul Muarif regarding using APE during learning, the PAUD has used several APEs in learning. However, the APE used was not adequate to train fine motor development and did not vary to attract children's interest. The purpose of the study was to develop and see the feasibility of APE Multifunction Beams in developing fine motor skills for children aged 4-5 years. The type of research used is Research and Development (R&D) using the ADDIE model using Dick and Carey Theory which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. With instrument validation sheet material experts and media experts as well as children's observation sheets. Based on the assessment of 2 APE validation and 2 material experts, for material expert validation the total scores from V1 and V2 are 69 and 67, so the maximum total score is 80, so that the percentage results are 80% and 86% which fall into the very feasible category. While the APE validation scores V1 and V2 are 69 and 67, the number of frequencies is 16, so that the percentage results are 86.25% and 83.75% which are in the very feasible category. Then for the results of the observation sheet the child's fine motor skills got a score from the validator of 308, with the number of questions as many as 5 multiplied by 15 children, then the ideal total score obtained was 375 so as to obtain a percentage result of 82.13% which was included in the very feasible category. Based on these results, it can be concluded that the multifunctional APE beam can develop fine motor skills for children aged 4-5 years and is very suitable for use in the learning process.